Differentiation between vestibular schwannomas and meningiomas with atypical appearance using diffusion kurtosis imaging and three-dimensional arterial spin labeling imaging. Issue 109 (December 2018) - Lin, Lin; Chen, Xiaodan; Jiang, Rifeng; Zhong, Tianjin; Du, Xiaoqiang; Xu, Ganggang; Duan, Qing; Xue, Yunjing
Abstract: Purpose: An accurate differentiation between vestibular schwannomas (VS) and meningiomas is critical in determining treatment strategies and clinical prognoses. However, misdiagnoses may occur when typical imaging appearances are absent. The purpose of this study was to assess the performances of diffusion kurtosis imaging (DKI) and three-dimensional arterial spin labeling imaging (3D-ASL) in the differentiation of VS and meningiomas with atypical appearance. Materials and methods: Thirty-eight patients with pathologically proven VS and meningiomas were consecutively enrolled. All patients had no typical appearance and underwent DKI and 3D-ASL scan. Then, the DKI and 3D-ASL parameters were measured. Statistical analyses were performed using independent-sample t-tests, Mann-Whitney U tests and receiver operating characteristic (ROC) curve analyses. Results: Mean kurtosis (MK), radial kurtosis (RK), axial kurtosis (AK), fractional anisotropy (FA) and cerebral blood flow (CBF) were significantly lower in VS than those in meningiomas, mean diffusivity (MD) were significantly higher in VS than that in meningiomas (all P < 0.05). ROC curve analyses showed that the diagnostic performance of kurtosis values outperformed those of other MR parameters. A cut-off RK value of 0.766 yielded a sensitivity of 91.67%, a specificity of 100.0%, and an accuracy of 94.74%, with an AUC of 0.988. Conclusion: DKI and 3D-ASL are useful for differentiating VS and meningiomas with atypical appearance, with kurtosis values of DKI have the best diagnostic efficiency.